2018
DOI: 10.1016/j.physa.2018.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Spectral density and calculation of free energy

Abstract: For planar and cubic Ising models, we examined two ways of approximation of a spectral density that describes a degeneracy of energy levels. We approximated the exponent of the spectral density by polynomials of even degrees and using our n-vicinity method [8,9]. According our analysis, the free energy is almost independent of the chosen method of approximation. However, its derivatives depend on the way of approximation and substantially differ in the neighborhood of a critical temperature. Our calculations s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Более того, к настоящему времени вид распределения энергий известен только для одномерной модели Изинга. Это обстоятельство инициировало ряд работ, авторы которых пытаются получить выражения для распределения энергий в рамках различных приближений и численными методами [8][9][10][11][12][13].…”
Section: физикаunclassified
“…Более того, к настоящему времени вид распределения энергий известен только для одномерной модели Изинга. Это обстоятельство инициировало ряд работ, авторы которых пытаются получить выражения для распределения энергий в рамках различных приближений и численными методами [8][9][10][11][12][13].…”
Section: физикаunclassified
“…In Ref. [6] we showed that if 0 E is the energy of the ground state and the total density is an exponent…”
mentioning
confidence: 99%